Paint -- products and applications; protective coatings; pipeline coatings - Materials, American Society for Testing & ([S.l.] : ASTM, 2009)
Covers architectural finishes and paint products, such as traffic coatings, marine coatings, industrial protective coatings, and masonry treatments.